Ecofriendly management of root-knot nematode in chilli and okra - Singh, Satyendra; Sellaperumal, C.; T., Manjunatha Gowda; Rai, A. B.; Singh, B. (Indian Horticulture, 2019)
Root-knot nematode species especially Meloidogyne incognita and Meloidogyne javanica are most widespread and economically important, frequently causing severe damage in chilli and okra resulting in losses of 12.85 and 14.10%, respectively in the country. The withdrawal of many nematicides and soil fumigants due to their high toxic residual effects requires an urgent need to develop alternative strategies for the management of nematodes. In this endeavour, ICAR-IIVR tested combined application of botanicals (neem cake, Mexican poppy) and bioagents (Trichoderma viride, Pochonia chlamy dosporia, Purpureocillium lilacinum, Paecilomyces lilacinus, Pseudomonas fluorescens) were highly effective against M. incognita in these crops which can be taken advantage in the pest management.